Cognitive Analysis of Metonymy in Classical Chinese Poetry - Li, Wei (International Journal of Linguistics, 2023)
Although metonymy is widespread in poetry, it has been ignored compared to the attention that has been paid to metaphor. Metonymy is not only a figure of speech, but also a cognitive means by which one conceptual entity offers mental access to another conceptual entity. In poetry, metonymy, as a linguistic device, is able to construct rich meanings and aesthetic effects and thus highlight the theme. What’s more, metonymy is able to reveal the cognitive process by which the poet perceives and thinks about the world. As for readers, their decoding of poetry is partly dependent on their mental processing of metonymy. Metonymy in classical Chinese poetry is culturally and historically situated. Thus, metonymy is a vehicle for cultural and historical information. The exploration of metonymy in classical Chinese poetry is aimed to offer a new perspective of metonymy for literary studies.